Time Characteristics of the Influence Radius by Injecting N2 to Displace Coalbed Methane: A Case Study. (7th February 2019) - Li-wei, Chen; Tian-hong, Yang; Hong-min, Yang; Li-guo, Wang
Abstract : Injecting N2 to displace methane is an effective way to enhance coalbed methane drainage, and the influence radius of this process is an important factor in borehole arrangement. To determine reasonable spacing between injection boreholes and discharge boreholes, experimental and theoretical studies were carried out. The change of rule for the influence radius was determined based on the flow rate changes at the discharge boreholes when injecting gas into a coal seam in the field. Based on gas seepage-diffusion theory, a model for injecting N2 to displace coalbed methane was established. Through numerical simulation, the time characteristics of the influence radius were analyzed. The results show the following: Under different gas injection pressure conditions, the influence radius increases exponentially as injection time increases, but the rate of increase of the influence radius decreases gradually. For the same injection time, the higher the injection pressure, the wider the influence radius will be. After obtaining field results, regression analysis was applied to analyze the numerical results of gas injection at different pressures, and then, the quantitative relationship between the injection influence radiusr, the injection timet, and the injection pressurep was found. According to the results calculated using this formula at an injection pressure of 0.5 MPa, the optimum spacing between boreholes was determined to be 1.5 m at the Shigang Coal Mine. The analysis of reasonable spacing between injection and extraction boreholes at different injection pressures shows that the reasonable spacing between boreholes was linearly correlated with gas injection pressures. This study has important theoretical and practical significance for the spacing between boreholes in a reasonable arrangement when injecting N2 to displace methane.